2020
DOI: 10.1002/cbic.202000233
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Border: From Keto‐ to Imine Reduction in Short‐Chain Dehydrogenases/Reductases

Abstract: The family of NAD(P)H‐dependent short‐chain dehydrogenases/reductases (SDRs) comprises numerous biocatalysts capable of C=O or C=C reduction. The highly homologous noroxomaritidine reductase (NR) from Narcissus sp. aff. pseudonarcissus and Zt_SDR from Zephyranthes treatiae, however, are SDRs with an extended imine substrate scope. Comparison with a similar SDR from Asparagus officinalis (Ao_SDR) exhibiting keto‐reducing activity, yet negligible imine‐reducing capability, and mining the Short‐Chain Dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
(41 reference statements)
0
15
0
5
Order By: Relevance
“…As these principles might also apply to other NAD(P)H-dependent oxidoreductases, our model could support enzyme discovery, add to the diversity of imine-reducing enzymes, and contribute to rational enzyme engineering approaches toward imine reduction. [52]…”
Section: Resultsmentioning
confidence: 99%
“…As these principles might also apply to other NAD(P)H-dependent oxidoreductases, our model could support enzyme discovery, add to the diversity of imine-reducing enzymes, and contribute to rational enzyme engineering approaches toward imine reduction. [52]…”
Section: Resultsmentioning
confidence: 99%
“…These flank the active site and mediate the local electrostatic fine‐tuning of the catalytic residues [36] . Exchanging several flanking residues in a dehydrogenase with distinct carbonyl‐reducing activity resulted in a promiscuous enzyme with imine‐reducing activity [37] . Recently, three new imine‐reducing enzymes were generated by introducing single‐point mutations into βHADs, including the exchange of the proton donor and the removal of a bulky gate‐keeping residue [38] .…”
Section: Methodsmentioning
confidence: 99%
“…[36] Exchanging several flanking residues in a dehydrogenase with distinct carbonyl-reducing activity resulted in a promiscuous enzyme with imine-reducing activity. [37] Recently, three new imine-reducing enzymes were generated by introducing singlepoint mutations into βHADs, including the exchange of the proton donor and the removal of a bulky gate-keeping residue. [38] To access imine reduction in the glyoxylate reductase from Arabidopsis thaliana (At-βHAD), the catalytically essential lysine at position 170 (K170) was exchanged by aspartic acid.…”
mentioning
confidence: 99%
“…Furthermore, a SDR from Methylobacterium sp. 77 that only exhibits ketoreductase activity was recently engineered to gain imine reductase activity by introducing four mutations in its active site to resemble some of the structural features of the NR reductase [18] . Notably, in all of these cases, the ketoreductase and the imine reductase activities were strictly substrate dependent; furthermore, the SDR enzymes were active toward pre‐formed (cyclic) imines but reductive amination between a carbonyl compound and an amine donor was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…77 that only exhibits ketoreductase activity was recently engineered to gain imine reductase activity by introducing four mutations in its active site to resemble some of the structural features of the NR reductase. [18] Notably,i na ll of these cases, the ketoreductase and the imine reductasea ctivities were strictly substrate dependent;f urthermore, the SDR enzymes were active toward preformed (cyclic) imines but reductive amination between ac arbonyl compound and an amine donor was not reported. Conversely, other groupsh ave independently reported that few imine reductases (IReds)a nd reductivea minases (RedAms) possess promiscuousk etoreductasea ctivity on very specific substrates such as tri-, di-andm ono-fluorinated acetophenones at the terminalcarbon position.…”
Section: Introductionmentioning
confidence: 99%